Magnetoreception in birds: II. Behavioural experiments concerning the cryptochrome cycle - Wiltschko, Roswitha (J Exp Biol, 2014)
Behavioural tests of the magnetic compass of birds and corresponding immunohistological studies on the activation of retinal cryptochrome 1a, the putative receptor molecule, showed oriented behaviour and activated Cry1a under 373 nm UV, 424 nm blue, 502 nm turquoise and 565 nm green light, although the last wavelength does not allow the first step of photoreduction of cryptochrome to the semiquinone form. The tested birds had been kept under ‘white’ light before, hence we suggested that there was a supply of semiquinone present at the beginning of the exposure to green light that could be further reduced and then re-oxidized. To test the hypothesis in behavioural experiments, we tested robins, Erithacus rubecula, under various wavelengths (1) after 1 h pre-exposure to total darkness and (2) after 1 h pre-exposure to the same light as used in the test. The birds were oriented under blue and turquoise light, where the full cryptochrome cycle can run, but not under green light. This finding is in agreement with the hypothesis. Orientation under green light appears to be a transient phenomenon until the supply of semiquinone is depleted.